Development and religion : theology and practice - Clarke, Matthew , 1969- (Edward Elgar, 2011)
Development and Religion explores how the world's five major religions - Hinduism, Buddhism, Judaism, Christianity and Islam - understand and practice 'development' through an examination of their sacred texts, social teaching and basic beliefs